The Different impacts of video production practices on filmmakers and filmed subjects in the “end-of-life care” documentaries filmed Zhejiang Communication University - Guanghe, Ge; Shazleen Mohamed,; Muhammad Nurhafiz Hassim,; Wenting, Wang (Penerbit Universiti Kebangsaan Malaysia, 2024)
Most of the current video production practices are focusing on filming, editing, storytelling or special effects, and the articles on video production also put the emphasis on tourism, business or natural scenery. There are not many video production practices on topics such as hospice, because this topic involves death, illness, patients and their families and other factors, and most of these film subjects are not willing to be shot. This research aims to explore the impact of filming practices on sensitive topics on the producers and the filmed subjects. By selecting the hospice care documentaries produced by Zhejiang Communication University as a case study, this study interviews 8 documentary producers and 8 filmed subjects and researchs the whole filming process through method of participatory observation. This research demonstrates that for hospice documentary filmmakers, going through such a filmmaking journey can be helpful in increasing their level of identification with hospice care, increasing their emotional experience and documentary production skills, and most importantly for their future documentary filmmaking, as they feel the power of humanity. For the subjects, i.e. patients, families, doctors and nurses, end-of-life care documentaries have expanded the dissemination of knowledge to a certain extent, but the impact on the behavioural choices of patients at the moment of death has not been significant, and these behavioural choices are more influenced by non-medical factors which the filmmakers are clearly aware of it. Instead, these filming activities were somewhat of an optional burden on filmed subjects.